2014
DOI: 10.1016/j.neuropsychologia.2014.08.008
|View full text |Cite|
|
Sign up to set email alerts
|

Rhythmicity and cross-modal temporal cues facilitate detection

Abstract: Temporal structure in the environment often has predictive value for anticipating the occurrence of forthcoming events. In this study we investigated the influence of two types of predictive temporal information on the perception of near-threshold auditory stimuli: 1) intrinsic temporal rhythmicity within an auditory stimulus stream and 2) temporally-predictive visual cues. We hypothesized that combining predictive temporal information within- and across-modality should decrease the threshold at which sounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 83 publications
7
48
1
Order By: Relevance
“…A recent study (62) showed that rhythmicity (i.e., high temporal predictability) enhances detection, confirming a link between temporal and content processing. Similar effects occur in vision: reaction time in a detection task is modulated by the phase of delta oscillations (63).…”
Section: Discussionmentioning
confidence: 81%
“…A recent study (62) showed that rhythmicity (i.e., high temporal predictability) enhances detection, confirming a link between temporal and content processing. Similar effects occur in vision: reaction time in a detection task is modulated by the phase of delta oscillations (63).…”
Section: Discussionmentioning
confidence: 81%
“…When helpful to the goal-directed behaviour, regular/predictable stimuli will be continuously processed (i.e., selected) and utilised by the brain (e.g., Ten Oever et al 2014). However, stimulus regularity likewise seems to enable the observer to effectively inhibit irrelevant stimuli in situations where they are highly unlikely to directly facilitate the ongoing behaviour, e.g., in no-task setups, as in the current experiment.…”
Section: The Importance Of Context-based Control For Information Procmentioning
confidence: 82%
“…In the case of naturalistic stimuli, e.g., speech, the natural delay between the visual and the subsequent auditory input is well known to facilitate comprehension (e.g., van Wassenhove et al, 2005). Recently, the mechanisms have been revealed by which a cross-talk between higher-level (language and top-down attention areas) areas and lower-level auditory cortices enables, currently unattended but potentially important, stimuli to become attended in realworld like, multi-speaker settings (i.e., the 'cocktail party' context; Zion-Golumbic et al, 2014). The fact that the present effects, obtained with simple acoustic information (tones), were localised to lateral occipital cortices is consistent with these findings and supports the notion of a privileged interplay between auditory cortices, involved in complex sound recognition (and, perhaps, also localisation), and visual cortices, involved in visual-object identification (often person recognition) (e.g., Blank et al, 2014).…”
Section: The Importance Of Context-based Control For Information Procmentioning
confidence: 99%
See 2 more Smart Citations